Bleeding and related mortality with NOACs and VKAs in newly diagnosed atrial fibrillation: results from the GARFIELD-AF registry - Bassand, Jean-Pierre; Virdone, Saverio; Badoz, Marc; Verheugt, Freek W. A.; Camm, A. John; Cools, Frank; Fox, Keith A. A.; Goldhaber, Samuel Z.; Goto, Shinya; Haas, Sylvia; Hacke, Werner; Kayani, Gloria; et al. (Blood advances, 2021)
In atrial fibrillation (AF), lower risks of death and bleeding with non-vitamin-K oral anticoagulants (NOACs) were reported in meta-analyses of controlled trials, but whether these findings hold true in real-world practice remains uncertain. Risks of bleeding and death were assessed in 52 032 patients with newly diagnosed AF enrolled in GARFIELD-AF (Global Anticoagulant Registry in the FIELD-Atrial Fibrillation), a worldwide prospective registry. Baseline treatment was vitamin K antagonists (VKAs) with or without antiplatelet (AP) agents (VKA ± AP) (20 151; 39.3%), NOACs ± AP agents (14 103; 27.5%), AP agents only (10 748; 21.0%), or no antithrombotics (6219; 12.1%). One-year follow-up event rates (95% confidence interval [CI]) of minor, clinically relevant nonmajor (CRNM), and major bleedings were 2.29 (2.16-2.43), 1.10 (1.01-1.20), and 1.31 (1.21-1.41) per 100 patient-years, respectively. Bleeding risk was lower with NOACs than VKAs for any bleeding (hazard ratio (HR) [95% CI]), 0.85 [0.73-0.98]) or major bleeding (0.79 [0.60-1.04]). Compared with no bleeding, the risk of death was higher with minor bleeding (adjusted HR [aHR], 1.53 [1.07-2.19]), CRNM bleeding (aHR, 2.59 [1.80-3.73]), and major bleeding (aHR, 8.24 [6.76-10.04]). The all-cause mortality rate was lower with NOACs than with VKAs (aHR, 0.73 [0.62-0.85]). Forty-five percent (114) of all deaths occurred within 30 days, and 40% of these were from intracranial/intraspinal hemorrhage (ICH). The rates of any bleeding and all-cause death were lower with NOACs than with VKAs. Major bleeding was associated with the highest risk of death. CRNM bleeding and minor bleeding were associated with a higher risk of death compared to no bleeding. Death within 30 days after a major bleed was most frequently related to ICH. This trial was registered at www.clinicaltrials.gov as #NCT01090362.
Gesehen am 02.03.2021